Olfactory testing combined with dopamine transporter imaging as a method to detect prodromal Parkinson's disease. Issue 4 (3rd December 2009) - Ponsen, Mirthe M; Stoffers, Diederick; Wolters, Erik Ch; Booij, Jan; Berendse, Henk W
Abstract : Objective: Olfactory dysfunction is an early and common symptom in Parkinson disease (PD). Previously, the authors demonstrated that idiopathic olfactory dysfunction in first-degree relatives of PD patients is associated with an increased risk of developing PD within 2 years. The aim of the present study was to determine the value of combined olfactory testing and SPECT scanning in predicting future PD in the same population of relatives over a 5-year period. Methods: In a cohort of 361 non-parkinsonian, non-demented first-degree relatives of PD patients, a combination of olfactory processing tasks was used to select groups of hyposmic (n=40) and normosmic (n=38) individuals for a 5-year clinical follow-up evaluation and sequential SPECT scanning, using a dopamine transporter ligand to assess nigrostriatal dopaminergic function at baseline and 5 years from baseline. A validated questionnaire, sensitive to the presence of parkinsonism, was used in the follow-up of the remaining 283 relatives. Results: Five years from baseline, five out of the 40 hyposmic relatives fulfilled clinical diagnostic criteria for PD. None of the other 349 relatives available for follow-up developed PD. All hyposmic individuals developing PD had an abnormal baseline SPECT scan. Discussion: In conclusion, idiopathic hyposmia in first-degree relatives of PD patients is associated with an increased risk of developing clinical PD of 12.5% over a 5-year period. The present data suggest that a two-step approach using olfactory testing followed by SPECT scanning in hyposmic individuals has a very high sensitivity and specificity in detecting PD. The usefulness of this two-step approach needs to be confirmed in larger populations.